Characterizing the Exception Handling Code of Android Apps - Queiroz, Francisco Diogo; Coelho, Roberta (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2016)
Android apps are becoming more and morepopular. The number of such apps is astonishinglyincreasing in a daily rate, as well as the number of usersaffected by their crashes. Android apps as other Java appsmay crash due to faults on the exception handling (EH) code(e.g. uncaught exceptions). Techniques for exceptiondetection and handling are not an optional add-on but afundamental part of such apps. Yet, no study hasinvestigated the main characteristics of the EH code ofmobile apps nor the developers perspective about the goodand bad practices of EH in such context. This paper reportstwo complementary studies: one that inspected the EH codeof 15 popular Android apps (which overall comprises of 3490try-catch-finally blocks), and other study which surveyed 47Android experts to get their opinion about the good and badpractices of EH development in Android environment. Someoutcomes of the studies shows a high occurrence of exceptionswallowing and only few apps sending exception informationto a remote server – both considered by Android experts asbad practices that negatively impact the app robustness.